A multicompartment vascular implant of electrospun wintergreen oil/ polycaprolactone fibers coated with poly(ethylene oxide) - Shima Eldurini (Elsevier, 2021)
Background: The aim of the present study was to fabricate double layered scaffolds of electrospun polycaprolactone (PCL) and poly(ethylene oxide) (PEO). The electrospun PCL fibers were functionalized with wintergreen oil (WO) as a novel approach to prevent vascular grafts failure due to thrombosis by adjusting biomaterial–blood interactions. Methods: PCL tubular scaffolds were prepared by electrospinning approach and coated with PEO as a hydrophilic polymer. The single and double layered scaffolds were characterized in terms of their morphological, chemical properties -as well as-hemocompatibility assays (i.e. prothrombin time, hemolysis percentage and platelets adhesion). Moreover, the antioxidant potential of WO-PCL samples were measured by 2,2-diphenyl-1-picrylhydrazyl hydrate (DPPH) free radical assay. Results: The results demonstrated that incorporation of WO during the electrospinning process decreased the PCL fiber diameter. In addition, the prothrombine time assay shows that WO could be used to lower the electrospun PCL fiber tendency to induce blood clotting. Moreover, SEM observations of platelets adhesion of both single and double layered PCL/PEO scaffolds fiber shows an increase of platelets number, compared with the scaffolds containing WO. Conclusions: The antioxidant potential and blood compatibility measurements of WO-PCL/PEO samples highlight the approach made so far as an ideal synthetic small size vascular grafts to overcome autogenous grafts shortages and drawbacks.